GelInsight: Open-source software for large-sample DNA fragmentation quality control in gel electrophoresis images - Kathlyne Jayne B. Bautista; Marjan Mehrab-Mohseni; Sultan A. Kiradoh; Paul A. Dayton; Samantha G. Pattenden (PLoS ONE, 2026)
High throughput DNA fragmentation technology for next generation sequencing have become widely available, but there remains a need for affordable and efficient DNA fragmentation pattern analysis. Commercial electrophoresis platforms, such as the TapeStation, are costly, time-consuming, and have limited batch-processing capabilities. Traditional gel electrophoresis provides a low-cost, high-throughput alternative. However, existing open-source software, such as ImageJ, for gel electrophoresis image analysis typically requires extensive manual pre-processing and yields limited quantitative metrics relevant to DNA fragmentation quality control. Here, we have developed an open-source MATLAB-based software, GelInsight , for bulk analysis of gel electrophoresis images for analysis and quality control of DNA fragmentation patterns. GelInsight integrates automated image and signal processing tools to determine the base pair size distribution of each sample and to calculate key quality control metrics, including multiple peak base pair sizes and base pair size percentage within a specified range. A user-friendly graphical user interface facilitates efficient data interaction and comprehensive visualization of the analytical outputs. The quantification accuracy of GelInsight , including peak base-pair accuracy and relative area measurements, is consistent with both existing open-source software (within 2 ± 2 bp) and commercial assays (within 64 ± 24 bp). Overall, this automated tool streamlines gel image analysis and enhances reproducibility and quantitative rigor in assessing DNA fragmentation patterns.